Design and Evaluation of 3-in-1 Volleyball Self-Training Machine - Jusoh, Nur Hazwanie; Rusdan, NurFatin Anisa; Abd Hamid, Nurul Syazwani; Wagiman, Abdullah (Multidisciplinary Applied Research and Innovation, 2025)
Volleyball training often requires specialized equipment to enhance skill development. However, existing self-training tools are limited in functionality and accessibility, making comprehensive training challenging for individual players. This project aims to develop a 3-in-1, setter, spike and digging volleyball self-training machine to provide a cost-effective and efficient solution for individual training. The methodology involves a systematic review of existing training tools, followed by a structured design and development process. The design was refined through simulations to validate theoretical functionality. The performance tests including oscillation, accuracy, and stability assessments were conducted to evaluate effectiveness. The results demonstrate that the proposed device significantly improves skill acquisition by enabling repetitive and controlled practice of multiple volleyball techniques. The stability test confirms the machine can support up to 20kg, ensuring safe usage. In conclusion, the developed 2-in-1 volleyball self-training machine enhances training efficiency and accessibility by integrating multiple functions into a single device.